Regional cortical perfusion increases induced by a 6-month endurance training in young sedentary adults - Upadhyay, Neeraj; Schörkmaier, Theresa; Maurer, Angelika; Claus, Jannik; Scheef, Lukas; Daamen, Marcel; Martin, Jason A.; Stirnberg, Rüdiger; Radbruch, Alexander; Attenberger, Ulrike; Stöcker, Tony; Boecker, Henning (Frontiers in Aging Neuroscience, 2022)
Physical inactivity is documented as health risk factor for chronic diseases, accelerated aging and cognitive impairment. Physical exercise, on the other hand, plays an important role in healthy aging by promoting positive muscular, cardiovascular and central nervous system adaptions. Prior studies on the effects of exercise training on cerebral perfusion have focused largely on elderly cohorts or patient cohorts, while perfusion effects of exercise training in young sedentary adults have not yet been fully assessed. Therefore, the present study examined the physiological consequence of a six-month endurance exercise training on brain perfusion in 28 young sedentary adults randomly assigned to an intervention group (IG; regular physical exercise) or a control group (CG; without physical exercise). The IG performed an extensive running interval training three times per week over 6 months. Performance diagnostics and MRI were performed every two months and training intensity was adapted individually. Brain perfusion measurements with pseudo-continuous arterial spin labeling was analyzed using the standard Oxford ASL pipeline. A significant interaction effect between group and time was found for right superior temporal gyrus (STG) perfusion, driven by an increase in the IG and a decrease in the CG. Furthermore, a significant time effect was observed in the right middle occipital region in the IG only. Perfusion increases in the right STG, in the ventral striatum, and in primary motor areas were significantly associated with increases in maximum oxygen uptake (VO2max). Overall, this study identified region-specific increases in local perfusion in a cohort of young adults that partly correlated with individual performance increases, hence, suggesting exercise dose dependency. Respective adaptations in brain perfusion are discussed in the context of physical exercise-induced vascular plasticity.